Diversão e juventudes em finais do século XIX: histórias registradas por memorialistas diamantinenses - Renata Cristina Simões de Oliveira (2022)
This research seeks to identify the ways in which young people from Diamantina born in the final decades of the 19th century had fun, observing, however, similarities and differences between them and in the description of entertainment practices disseminated in periodical sources. The thesis pursued here is that: how the ideas about modernity that were projected by the Diamantina elite influenced the imagination and writing of memoirists and writers, especially with regard to cultural aspects linked to entertainment. The main sources of the research were memoirists Ciro Arno, Helena Morley and Aristides Rabello. As sources of support, periodicals from the last two decades of the 19th century and the first of the 20th century, and other published memoirs. The Diamond context and research questions are addressed. Then there is the presentation of the three memoirists considering their background and the family context to which they belonged. Next, a separation is made between the entertainment spaces found in the authors' memories. First, the entertainment held inside homes. The dining rooms, the kitchen, the patio and the backyard were residential spaces that were sometimes occupied by parties with plenty of food and drinks and filled with orchestras or music bands, revealing that common practices inside the house also influenced the fun practices outside the home. And also the entertainment on the street. The liquor stores, the warehouses, the billiards, the theater and the use of the street as a space for occupation by the elite and the less privileged. The city's fields and rivers as places of contemplation and festive gatherings. It was revealed that the memoirists were influenced by the ideas projected at Diamantina, but they allowed themselves to express their points of view and the entertainment they had contact with, even those criticized in the local press. The sources also revealed that women were essential for organizing and carrying out entertainment, however, they were censored from participating freely in some of them, as were black women and men living in the city at that time.